2022
DOI: 10.3390/ijms23073824
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1 Targeted Lipopolyplexes as Vehicles for Efficient Delivery of shRNA-Runx2 to Osteoblast-Differentiated Valvular Interstitial Cells; Implications in Calcific Valve Disease Treatment

Abstract: Calcific aortic valve disease (CAVD) is a progressive inflammatory disorder characterized by extracellular matrix remodeling and valvular interstitial cells (VIC) osteodifferentiation leading to valve leaflets calcification and impairment movement. Runx2, the master transcription factor involved in VIC osteodifferentiation, modulates the expression of other osteogenic molecules. Previously, we have demonstrated that the osteoblastic phenotypic shift of cultured VIC is impeded by Runx2 silencing using fullerene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A previous study has shown that VCAM1 is highly expressed in the aortic valves of diabetic/atherosclerotic ApoE-deficient mice and is considered a potential target for nanocarriers developed to block the progression of AS [19]. VCAM1 is a transmembrane sialoglycoprotein that is often used for targeted drug delivery to endothelial cells due to its inducible expression on the cell surface in pathological conditions [20][21][22][23]. Moreover, there is an increased expression of VCAM1 in aortic valve interstitial cells after exposure to IFNγ-and lipopolysaccharide [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that VCAM1 is highly expressed in the aortic valves of diabetic/atherosclerotic ApoE-deficient mice and is considered a potential target for nanocarriers developed to block the progression of AS [19]. VCAM1 is a transmembrane sialoglycoprotein that is often used for targeted drug delivery to endothelial cells due to its inducible expression on the cell surface in pathological conditions [20][21][22][23]. Moreover, there is an increased expression of VCAM1 in aortic valve interstitial cells after exposure to IFNγ-and lipopolysaccharide [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is an increased expression of VCAM1 in aortic valve interstitial cells after exposure to IFNγ-and lipopolysaccharide [24]. Efficient drug delivery systems for AS using nanomedicine are currently being examined, with a particular focus on VCAM1-targeted PEGylated lipopolyplexes as a potential encapsulating drug delivery system [23]. However, translating this technology into clinical practice is difficult and may have serious limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Negative Staining Transmission Electron Microscopy: Transmission electron microscopy (TEM) was used to investigate the morphology of LN/SPMs, PEI-LN/SPMs, and Bio-LN/SPMs, as previously described. [52] The lipid nanoemulsions were diluted 1:5 in 2% paraformaldehyde (PFA) and deposited on formvar-coated copper grids that had been previously treated for 10 minutes (min) with 1% Alcian blue. The grids were examined using a LaB6 filament-equipped Tecnai G2 Spirit BioTWIN Transmission Electron Microscope (FEI Company, ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%